“Did They Review My Work Correctly?”: Students’ Perspectives towards the Implementation of Peer Review - Refanja Rahmatillah; Rizki Fajrita; Veni Nella Syahputri (IJELR: International Journal of Education, Language, and Religion, 2019)
The notion of utilizing peer review to assist student’s performance in English as a Foreign Language (EFL) classrooms has been the focus of research, yet there are still some shortcomings emerged in its implementation from both students’ and teachers’ sides. This study aims to determine students’ perspectives towards the implementation of peer review technique in their English writing class. The relevant data of this study are obtained by giving online survey questionnaire consisting of 14 questions regarding their perception towards the implementation of peer review technique in the students’ previous Argumentative Writingclassroom of Syiah Kuala University. The responses are analyzed by employing both of quantitative and qualitative method. The result of the analysis indicates that most of the students perceive that peer review is useful for the success of their learning, while at the same time 50% of them still get anxiety while giving feedback due to lack of English competence. Students’ responses also suggest that teacher intervention is the most essential factor in giving appropriate feedback since students are unconfident of their friends work and still favor teacher’s correction.